Determination of Trace Elements in Leach Solution by Flame Atomic Absorption Spectrometry After Pre-Concentration on Amberlite XAD-4 - BINGOL, D.; AKCAY, M. (Asian Journal of Chemistry, 2010)
A multi-elements pre-concentration method was proposed for determination of Cu, Ni, Co, Mn, Pb, Zn and Cr from leaching solutions by flame atomic absorption spectrometry (FAAS). It has been investigated the enrichment performance of the three complexing reagents i.e., [8-hydroxyquinoline (8-HQ), dithizone (DT) and sodium diethyldithiocarbamate (NaDDTC)] on Amberlite XAD-4 resin of the mentioned elements which are at or below the detection limits in FAAS. The aliquots of (5 or 10 g) fly ash were leached with 500 or 1000 mL chelating solutions at optimum pHs (8 for 8-HQ and DT and 4 for NaDDTC) for 15 min under magnetic stirring conditions. Then the leachates were passed through preconcentration column and eluted the elements 15 mL 1.0 M HNO3 in water:water (1:2) and determined the elements by FAAS. The satisfactory recoveries had been obtained from the multielement pre-concentration studies with dithizone on Amberlite XAD-4. The recoveries Pb, Co and Zn were higher than 90 %, while acceptable for other elements (82, 77 and 72 % for Cu, Ni and Mn, respectively) except Cr (46 %) with acceptable precisions [RSD under 10 % (N = 5)].